English Language Program Administration Leadership and Management in the 21st Century - Christison, MaryAnn; Stoller, Fredricka L. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This volume provides both practicing and aspiring Language Program Administrators with knowledge about the research and theory that underpin key topics in educational leadership, as well as practical guidance for the day-to-day management of language programs, including budgets, personnel, decision making, strategic planning, advocacy, and digital technologies. The volume brings together 46 authors and contributors with a vast array of experiences as administrators of English language teaching programs all over the world-in Asia; Australia; Europe; the Middle East; New Zealand; North, Central, and South America; South Africa; Turkey; and the United Kingdom. As the need for more qualified administrators and leaders has increased, more teacher education programs have added formal courses on leadership and program administration to their offerings. Educators teaching these courses will find this volume to be an excellent core text to support students in developing their knowledge of and skills for language program administration. All chapters are connected to the contemporary realities of language program administration, and they offer practical guidance to Language Program Administrators in ways that are adaptable to different administrative contexts globally.
1. Introduction -- Part I. Fundamentals of Language-Program Administration -- 2. Making the Transition: From Language Teacher to Program Administrator -- 3. Perceptions of Language Program Administrators' Most Important Responsibilities -- 4. Language Programs in Diverse Contexts: Voices of Language-Program Administrators -- Part II. Leadership in Language Programs -- 5. Becoming Strategic -- 6. Taking the Lead to Promote Innovation -- 7. The Promoter of Quality -- 8. Leading Language Programs with Intercultural Competence -- 9. Making Decisions: Navigating Challenges and Managing Crises -- 10. Engaging, Energizing, and Empowering Faculty -- 11. Advocating for Students and Language Programs -- Part III. Management in Language Programs -- 12. Communication Strategies for Effective Language-Program Administration -- 13. Personnel Matters: Revisited -- 14. Managing Technology: Feet on the Ground, Head in the Cloud -- 15. Managing Resources and Financial Planning -- 16. Managing Time -- Part IV. Best Practices in Language-Program Administration -- 17. Best Practices Based on 360+ Years of Administrative Experience.
Keywords: Language and languages -- Study and teaching; Applied linguistics; School management and organization; School administration; Education and state; Language Education; Applied Linguistics; Organization and Leadership; Education Policy